An achievable rate of large block-fading MIMO systems with no CSI via successive decoding - Müller, Ralf; Takeuchi, Keigo; Vehkaperä, Mikko; Tanaka, Toshiyuki (2010 20th International Symposium on Information Theory and Its Applications, ISITA 2010 and the 2010 20th International Symposium on Spread Spectrum Techniques and Applications, ISSSTA 2010, 2010)
A Rayleigh block-fading multiple-input multiple-output (MIMO) channel with channel state information (CSI) available neither to the transmitter nor to the receiver is considered. A lower bound on the capacity is formulated based on a successive decoding (SD) scheme. An analytical expression of the lower bound is derived in the large-system limit, by using the replica method. Furthermore, the achievable rate of the linear minimum mean-squared error (LMMSE) receiver with SD is also evaluated in the large-system limit. The lower bound is superior to the lower bound derived by Hassibi and Hochwald for all signal-to-noise ratios (SNRs). © 2010 IEEE.
Keywords: Channel estimation; Receivers; Signal to noise Ratio; Covariance Matrix; MIMO; Detectors; Equations